2020
DOI: 10.1016/j.ebiom.2020.102894
|View full text |Cite|
|
Sign up to set email alerts
|

Single oral dose for HIV pre or post-exposure prophylaxis: user desirability and biological efficacy in macaques

Abstract: Background Daily oral pre- or post-exposure prophylaxis (PrEP or PEP) is highly effective in preventing HIV infection. However, many people find it challenging to adhere to a daily oral regimen. Chemoprophylaxis with single oral doses of antiretroviral drugs taken before or after sex may better adapt to changing or unanticipated sexual practices and be a desirable alternative to daily PrEP or PEP. We investigated willingness to use a single oral pill before or after sex among men who have sex with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…This could also cut the costs of ARV-based HIV prevention for some populations. New single dose post-exposure prophylaxis could therefore be a significant advance for many people [ 44 ].…”
Section: The New Target and Approaches For Hiv Preventionmentioning
confidence: 99%
“…This could also cut the costs of ARV-based HIV prevention for some populations. New single dose post-exposure prophylaxis could therefore be a significant advance for many people [ 44 ].…”
Section: The New Target and Approaches For Hiv Preventionmentioning
confidence: 99%
“…In many countries, tenofovir disoproxil fumarate (TDF)/emtricitabine (FTC) is the preferred backbone drug ( 57 , 58 ). However, in the MSM population, the vast majority of MSM prefer to use a single dose of PEP as opposed to a multitablet regimen formulation, and single-dose regimens show better adherence ( 59 , 60 ). An optimized regimen with good tolerability and simplified use improves PEP adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a recent report examining one- and two-dose schedules of FTC/TAF in combination with a cobicistat-boosted integrase inhibitor, elvitegravir, similarly demonstrated that an NRTI plus an INSTI regimen provides protective benefit as both PrEP and PEP, where the time to treatment initiation postexposure correlates with the level of protection. 34 …”
Section: Discussionmentioning
confidence: 99%